CEGAH STUNTING MELALUI DEMONSTRASI PMT BERBASIS PANGAN LOKAL PADA IBU BALITA DI WILAYAH KERJA PUSKESMAS ANTANG - Irma Irma; MAHENDRI DEAYU PUTRI; Yade K. Yasin; Arinie Tri Nurrahmi (PT Ininnawa Paramacitra Edu, 2026)
Stunting remains a significant nutritional problem in Indonesia, caused by long-term inadequate nutrient intake and mothers’ limited knowledge of appropriate feeding practices for toddlers. Prevention efforts can be carried out through effective and practical nutrition education, including demonstrations of complementary feeding (PMT) using locally sourced foods. This activity aimed to improve the knowledge and skills of mothers of toddlers in applying balanced nutrition principles to support child growth. The methods included nutrition education and practical demonstrations of PMT preparation. Evaluation was conducted using pre- and post-tests to assess changes in knowledge, along with observations of participant engagement. The results showed a significant increase in knowledge; prior to the intervention, most respondents were categorized as having inadequate and adequate knowledge, whereas after the intervention, the majority were classified as having good and very good knowledge. Practical demonstrations also improved mothers’ skills in preparing nutritious meals suited to their children’s needs. However, behavioral changes were not yet optimal due to habits, socioeconomic factors, and the limited duration of the intervention. Overall, this activity was effective and has the potential to be developed into a sustainable program.